Para além de Deus e da natureza: Elementos de filosofia trágica nos diálogos sobre a religião de David Hume - Silva, Gilberto Cabral da (2005)
This Work intends an epistemological approach of David Hume s Dialogues Concerning Natural Religion by French philosopher Clément Rosset s category of tragic philosophy . We propose a new interpretative possibility of Hume s thought in the Dialogues, different form the naturalism and beyond the simple skepticism . The concept of tragic philosophy allows one to think the Dialogues Concerning Natural Religion as a work of tragic philosophy, in which the concept of nature is completely dissolved by the skeptic arguments.